Leigh Hunt and the London literary scene : a reception history of his major works, 1805-1828 - Sinatra, Michael E., 1971- (Routledge studies in romanticism, 2005)
Leigh Hunt and the London Literary Scene reassesses Hunt's substantial contributions to several different genres and to offer an account of their significant impact on audiences during the Romantic period.